Jewish Orthodoxy in Scotland : Rabbi Dr Salis Daiches and religious leadership - Holtschneider, K. Hannah, 1971- (Scottish religious cultures., 2019)
Jews acculturated to Scotland within one generation and quickly inflected Jewish culture in a Scottish idiom. This book analyses the religious aspects of this transition through a transnational perspective on migration in the first three decades of the twentieth century.